A penetrating type epoxy resin adhesive, its preparation method and application

CN123004285APending Publication Date: 2026-10-30HUNAN MAGPOW ADHESIVE INDS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611337556.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有技术单纯依靠单一种类活性稀释剂降粘,会造成交联密度下降,固化后剪切强度明显降低;如果使用高分子量环氧树脂,粘度超过 50mPas,渗透能力不足,只能停留在石材表面,加固效果差

Benefits of technology

(1)针对现有环氧树脂石材修补面胶中存在的难以同时实现低渗透粘度、水下环境固化、固化制品无色透明、长期耐黄变、高光泽、硬度可控与高剪切粘接强度的技术缺陷,本发明创造性的提出了一种渗透型环氧树脂胶粘剂,采用双酚F型环氧树脂搭配双酚A型环氧树脂与三羟甲基丙烷三丙烯酸酯复配为主基体,并采用两种无色透明的AGE和苄基缩水甘油醚复配而成的活性稀释剂,搭配改性脂环胺含水潮湿固化体系,辅以折光匹配硅烷活化气相纳米二氧化硅作为补强填料,复配紫外吸收剂与受阻胺光稳定剂构成耐黄变体系,配合无色透明抗水解助剂、透明柔性增韧剂,构建双组份环氧胶粘剂体系,并且在这些组分的共同作用下,使得渗透型环氧树脂胶粘剂兼具低粘度、高渗透性、高剪切强度、可水中和潮湿固化、固化制品无色透明且耐黄变性能优异、光泽度高、硬度适中等优点,具体的,25℃粘度 20-35mPas,剪切强度(24h)≥8.5MPa,可在含水潮湿条件下完成固化,固化膜无色透明、无发白、不起泡,固化产物光泽度大于 100GS,邵氏硬度控制在 70-80D。同时,本发明的渗透型环氧树脂胶粘剂对大理石、花岗岩等天然石材具备良好微孔渗透能力,适用于潮湿基面、水下石材粘接、裂缝修补、微孔加固、饰面修复,胶层无色透明、长期使用不易黄变,不遮挡石材天然纹理,兼顾粘接强度、韧性以及长期装饰外观,原料易得,适合工业化生产。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a penetrating type epoxy resin adhesive as well as a preparation method and application thereof. The penetrating type epoxy resin adhesive adopts bisphenol F type, bisphenol A type epoxy resin and trimethylolpropane triacrylate as a main matrix, AGE and benzyl glycidyl ether as active diluents, a modified alicyclic amine curing system, a filler, a yellowing-resistant auxiliary agent, a hydrolysis-resistant auxiliary agent and a flexible toughening agent, and a two-component system is constructed. Under the joint action of the components, the penetrating type epoxy resin adhesive has the advantages of low viscosity, high permeability, high shear strength, water and moisture curing, colorless and transparent cured products, excellent yellowing resistance, high gloss, moderate hardness and the like, has good micropore penetration capacity for stone, is suitable for wet base surfaces, underwater stone bonding, crack repair, micropore reinforcement and surface repair, has a colorless and transparent adhesive layer, is not prone to yellowing during long-term use, does not shield the natural texture of stone, has bonding strength, toughness and long-term decorative appearance, raw materials are easy to obtain, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer adhesive technology, and relates to a penetrating epoxy resin adhesive, its preparation method and application. Background Technology

[0002] Natural marble and granite are widely used in architectural decoration and landscape water feature projects. The stone contains numerous micron-sized micropores and microcracks, requiring epoxy resin adhesives for penetration, reinforcement, bonding, and repair.

[0003] There are several technical contradictions in existing publicly available patents and commercially available epoxy adhesives for stone: First, achieving microporous penetration in stone requires a low-viscosity system. Current technologies that rely solely on a single type of reactive diluent to reduce viscosity result in decreased cross-linking density and a significant reduction in shear strength after curing. Furthermore, if high-molecular-weight epoxy resins are used, the viscosity exceeds 50 mPa. In some cases, the penetration ability is insufficient, and the resin can only remain on the surface of the stone, resulting in poor reinforcement. Furthermore, to address the above two issues, the applicant proposed a low-viscosity, hydrophilic curable epoxy resin stone repair adhesive, using high-molecular-weight hydrogenated bisphenol A epoxy resin as the matrix. While increasing the amount of diluent can reduce the viscosity of the adhesive, the excessive use of diluent not only fails to reduce costs but also makes it difficult to improve the shear strength after curing, leading to poor penetration and reinforcement.

[0004] Secondly, traditional polyamide curing systems generally have poor water resistance and are prone to yellowing when used outdoors for extended periods, making them unsuitable for long-term use in landscape water features. Furthermore, conventional cycloaliphatic amine systems, when poorly formulated, cannot achieve water-based interface curing, making it difficult to meet the needs of underwater repair work.

[0005] Third, conventional transparent epoxy adhesives generally have poor resistance to yellowing and are prone to yellowing after exposure to outdoor light or prolonged heating, which damages the decorative effect of stone surfaces; most high yellowing-resistant epoxy adhesives on the market have high viscosity and do not have the ability to penetrate and apply.

[0006] Fourth, existing epoxy systems often use bisphenol F type epoxy resin as the main raw material, resulting in high raw material costs. At the same time, the hardness of existing epoxy systems is polarized: high-bonding-strength products often have a Shore hardness greater than 80D, making the adhesive layer brittle; stone is subject to thermal expansion and contraction deformation, and hard adhesive layers are prone to cracking; after reducing the hardness, the shear strength drops to below 8MPa, which cannot meet the bonding requirements of engineering projects.

[0007] Fifth, conventional fillers have a large difference in refractive index compared to epoxy resin, resulting in a hazy, opaque adhesive layer after addition; poor dispersion of ordinary nanofillers can also cause the product to lose opacity, failing to meet the requirements for transparent repair finishes.

[0008] It is evident that the existing technology lacks a method that uses bisphenol F type epoxy resin and bisphenol A type epoxy resin as the matrix and also has low viscosity (≤30mPa). A penetrating epoxy resin adhesive with high permeability, high shear strength (≥8.5MPa), water-neutralized and moisture-cured, colorless and transparent cured products with excellent resistance to yellowing, high gloss (>100GS), and moderate hardness (Shore hardness of 70D~80D).

[0009] For the reasons stated above, this invention is proposed. Summary of the Invention

[0010] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a penetrating epoxy resin adhesive with low viscosity, high permeability, high shear strength, water-neutralization and moisture curing, colorless and transparent cured products with excellent yellowing resistance, high gloss and moderate hardness, as well as its preparation method and application.

[0011] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A penetrating epoxy resin adhesive, comprising component A and component B; Component A comprises the following raw material components in parts by weight: 15 to 25 parts of bisphenol F type epoxy resin 29 to 35 parts of bisphenol A type epoxy resin. 11 to 15 parts of trimethylolpropane triacrylate 12 to 18 parts of reactive diluent 3 to 6 parts of filler 1 to 2 parts of silane coupling agent; Defoamer 0.3 to 0.8 parts, 0.2 to 0.5 parts of wetting and dispersing agent; Yellowing resistance additive: 0.8 to 1.5 parts; Component B comprises the following raw material components in parts by weight: 70-80 parts of modified cycloaliphatic amine curing agent, 5 to 8 parts of curing accelerator, 8 to 12 parts toughening agent 2 to 4 parts of anti-hydrolysis additive; The active diluent is a compound of AGE and benzyl glycidyl ether; The yellowing resistance additive is a compound of hindered amine light stabilizer and benzotriazole UV absorber; The modified alicyclic amine curing agent is prepared from alicyclic amines and diluents as raw materials; The anti-hydrolysis agent is prepared from γ-aminopropyltriethoxysilane and a diluent.

[0012] In a further improvement of the above-mentioned penetrating epoxy resin adhesive, the epoxy equivalent of the bisphenol F type epoxy resin is 160 g / eq to 180 g / eq; and the epoxy equivalent of the bisphenol A type epoxy resin is 180 g / eq to 195 g / eq.

[0013] In a further improvement of the above-mentioned penetrating epoxy resin adhesive, the reactive diluent is composed of AGE and benzyl glycidyl ether in a mass ratio of 1.85 to 2.15:1.

[0014] In a further improvement of the above-mentioned penetrating epoxy resin adhesive, the filler is fumed nano-silica with a surface modified by a silane coupling agent; the particle size of the fumed nano-silica is 20 nm to 50 nm.

[0015] In a further improvement of the aforementioned penetrating epoxy resin adhesive, the silane coupling agent is KH-560; the defoamer is BYK-054; the wetting and dispersing agent is BYK-142; the mass ratio of the hindered amine light stabilizer to the benzotriazole UV absorber is 1:1; the hindered amine light stabilizer is UV-531; and the benzotriazole UV absorber is UV-1500.

[0016] The above-mentioned penetrating epoxy resin adhesive is further improved by a method for preparing the modified alicyclic amine curing agent, which includes the following steps: adding the alicyclic amine to a three-necked flask, starting the stirrer, controlling the rotation speed at 75 rpm to 85 rpm, adjusting the temperature at 60℃ to 65℃, adding the diluent dropwise over a time of 2 hours to 2.5 hours, adjusting the temperature to 65℃ to 70℃ after the addition is complete, continuing to stir for 1 hour to 1.5 hours, filtering, and obtaining the modified alicyclic amine curing agent; the weight ratio of the alicyclic amine to the diluent is 284:130; the alicyclic amine is 1,3-BAC; and the diluent is epoxy resin diluent 501.

[0017] In a further improvement of the above-mentioned penetrating epoxy resin adhesive, the curing accelerator is 2-ethyl-4-methylimidazole.

[0018] In a further improvement of the aforementioned penetrating epoxy resin adhesive, the toughening agent is polypropylene glycol diglycidyl ether.

[0019] The above-mentioned penetrating epoxy resin adhesive is further improved by the following steps in the preparation method of the anti-hydrolysis additive: γ-aminopropyltriethoxysilane is added to a three-necked flask, stirring is started, and a diluent is added in two portions, reacting for 20 minutes after each addition, and then filtered to obtain the anti-hydrolysis additive; the weight ratio of γ-aminopropyltriethoxysilane to diluent is 442:130; the diluent is epoxy resin diluent 501.

[0020] In a further improvement of the above-mentioned penetrating epoxy resin adhesive, the weight ratio of component A to component B is 3:1.

[0021] As a general technical concept, the present invention also provides a method for preparing the above-mentioned penetrating epoxy resin adhesive, comprising the following steps: S1. Under light-protected conditions, bisphenol F type epoxy resin, bisphenol A type epoxy resin, and trimethylolpropane triacrylate are mixed and stirred for 5 min to 20 min. An active diluent and a wetting and dispersing agent are added, the temperature is raised to 40℃ to 45℃, and the mixture is stirred for 20 min to 30 min. A filler, a silane coupling agent, a defoamer, and an anti-yellowing agent are added, and the mixture is stirred for 30 min to 40 min. The mixture is then cooled and filtered to obtain component A. Under light-protected conditions, a modified cycloaliphatic amine curing agent and an anti-hydrolysis agent are mixed and stirred for 10 min to 20 min. A curing accelerator and a toughening agent are added, and the mixture is stirred for 10 min to 30 min at a temperature of 40℃ to 45℃ to remove bubbles, thus obtaining component B. S2. Mix components A and B, stir for 3 to 5 minutes, let stand for 1 to 3 minutes to degas, and obtain a penetrating epoxy resin adhesive.

[0022] As a general technical concept, the present invention also provides an application of the above-described penetrating epoxy resin adhesive or the penetrating epoxy resin adhesive prepared by the above-described preparation method in stone processing.

[0023] The above-mentioned applications, in a further improvement, include at least one of bonding stone, repairing base surfaces, filling cracks, and brightening and repairing decorative surfaces; the stone includes at least one of marble and granite.

[0024] Compared with the prior art, the advantages of the present invention are as follows: (1) In view of the technical defects of existing epoxy resin stone repair adhesives, which are difficult to achieve simultaneously low penetration viscosity, underwater curing, colorless and transparent cured products, long-term resistance to yellowing, high gloss, controllable hardness and high shear bond strength, this invention creatively proposes a penetrating epoxy resin adhesive. It uses bisphenol F type epoxy resin combined with bisphenol A type epoxy resin and trimethylolpropane triacrylate as the main matrix, and uses two colorless and transparent AGE and benzyl glycidyl ether as reactive diluents, combined with modified cycloaliphatic amines in water-containing moisture curing. This epoxy resin adhesive system, supplemented with refractotropic silane-activated fumed silica as a reinforcing filler, and combined with UV absorbers and hindered amine light stabilizers to form a yellowing-resistant system, along with colorless and transparent anti-hydrolysis additives and transparent flexible toughening agents, constructs a two-component epoxy adhesive system. Under the combined action of these components, the penetrating epoxy resin adhesive possesses advantages such as low viscosity, high penetration, high shear strength, water neutralization and moisture curing, colorless and transparent cured products with excellent yellowing resistance, high gloss, and moderate hardness. Specifically, the viscosity at 25℃ is 20-35 mPa. The shear strength (24h) is ≥8.5MPa. It can be cured under moist conditions, producing a colorless, transparent, non-whitening, and non-bubbling cured film. The gloss of the cured product is greater than 100GS, and the Shore hardness is controlled at 70-80D. Furthermore, this penetrating epoxy resin adhesive exhibits excellent microporous penetration ability in natural stones such as marble and granite. It is suitable for bonding damp substrates and underwater stone, repairing cracks, reinforcing micropores, and restoring finishes. The adhesive layer is colorless and transparent, does not easily yellow over long-term use, does not obscure the natural texture of the stone, and balances bonding strength, toughness, and long-term decorative appearance. The raw materials are readily available, making it suitable for industrial production.

[0025] (2) The present invention also provides a method for preparing epoxy resin waterproof coating. The method adopts a combination of low temperature step feeding, light-avoiding gradient stirring and vacuum degassing process to prepare colorless and transparent penetrating epoxy adhesive that is resistant to yellowing for a long time. At the same time, the viscosity, penetration depth and mechanical strength of the finished product have small batch deviations, the process is stable, suitable for large-scale production and convenient for industrial application. Detailed Implementation

[0026] The present invention will be further described below with reference to specific preferred embodiments, but this does not limit the scope of protection of the present invention.

[0027] The raw materials and instruments used in the following examples are all commercially available; unless otherwise specified, the equipment and preparation processes used are conventional equipment and conventional processes.

[0028] Example 1 A penetrating epoxy resin adhesive, comprising component A and component B; Component A comprises the following raw material components by weight: 20 parts of bisphenol F type epoxy resin 32 parts of bisphenol A type epoxy resin. 13 parts of trimethylolpropane triacrylate 15 parts of reactive diluent 4 parts of filler 1.5 parts of silane coupling agent; 0.5 parts of defoamer 0.3 parts wetting and dispersing agent; 1.2 parts of yellowing resistance additive.

[0029] Component B comprises the following raw material components by weight: 75 parts of modified cycloaliphatic amine curing agent, 6 parts of curing accelerator 10 parts toughening agent Three parts of anti-hydrolysis additive. In this embodiment, the active diluent used is a compound of C12-14 alkyl glycidyl ether (AGE) and benzyl glycidyl ether, with a mass ratio of 2:1.

[0030] In this embodiment, the yellowing-resistant additive is composed of a hindered amine light stabilizer and a benzotriazole UV absorber in a mass ratio of 1:1.

[0031] In this embodiment, the epoxy equivalent of the bisphenol F type epoxy resin used is 160 g / eq to 180 g / eq.

[0032] In this embodiment, the epoxy equivalent of the bisphenol A type epoxy resin used is 180 g / eq to 195 g / eq.

[0033] In this embodiment, the filler used is fumed nano-silica modified with silane coupling agent, wherein the particle size of the fumed nano-silica is 20 nm to 50 nm.

[0034] In this embodiment, the silane coupling agent used is KH-560, a commercially available raw material, but it is not limited to this.

[0035] In this embodiment, the defoamer used is BYK-054, a commercially available raw material, but it is not limited to this.

[0036] In this embodiment, the wetting and dispersing agent used is BYK-142, a commercially available raw material, but it is not limited to this.

[0037] In this embodiment, the hindered amine light stabilizer used is UV-531, a commercially available raw material, but it is not limited to this.

[0038] In this embodiment, the benzotriazole UV absorber used is UV-1500, a commercially available raw material, but it is not limited to this.

[0039] In this embodiment, the modified cycloaliphatic amine curing agent is prepared from cycloaliphatic amine and diluent as raw materials. The preparation method includes the following steps: 1,3-BAC is added to a three-necked flask, stirring is started, the speed is controlled at 80 rpm, the temperature is adjusted to 60°C, epoxy resin diluent 501 is added dropwise, the dropping time is controlled at 2h, after the dropping is completed, the temperature is adjusted to 65°C, stirring is continued for 1.5h, and the mixture is filtered to obtain the modified cycloaliphatic amine curing agent, wherein the weight ratio of 1,3-BAC to epoxy resin diluent 501 is 284:130.

[0040] In this embodiment, the curing accelerator used is 2-ethyl-4-methylimidazole, a commercially available raw material, but not limited to this.

[0041] In this embodiment, the toughening agent used is polypropylene glycol diglycidyl ether, a commercially available raw material, but not limited to this.

[0042] In this embodiment, the anti-hydrolysis agent is prepared from γ-aminopropyltriethoxysilane and diluent as raw materials. The preparation method includes the following steps: γ-aminopropyltriethoxysilane is added to a three-necked flask, stirring is started, epoxy resin diluent 501 is added in two portions, and the reaction is carried out for 20 minutes after each addition. The mixture is then filtered to obtain the anti-hydrolysis agent, wherein the weight ratio of γ-aminopropyltriethoxysilane to epoxy resin diluent 501 is 442:130.

[0043] In this embodiment, the weight ratio of component A to component B is 3:1.

[0044] A method for preparing the penetrating epoxy resin adhesive described in this embodiment includes the following steps: S1. Under light-protected conditions, bisphenol F epoxy resin, bisphenol A epoxy resin, and trimethylolpropane triacrylate are mixed and stirred for 10 min. An reactive diluent (AGE and benzyl glycidyl ether) and a wetting and dispersing agent are added. The mixture is heated to 42°C and stirred for 25 min. A filler, silane coupling agent, defoamer, and anti-yellowing agent are added and stirred for 30 min. The mixture is then cooled and filtered to obtain component A. Under light-protected conditions, a modified cycloaliphatic amine curing agent and an anti-hydrolysis agent are mixed and stirred for 15 min. A curing accelerator and a toughening agent are added and stirred for 20 min at a constant temperature of 40°C. The mixture is then degassed under vacuum to obtain component B.

[0045] S2. Mix components A and B, stir for 4 minutes, let stand for 2 minutes, and degas under vacuum to obtain a penetrating epoxy resin adhesive.

[0046] An application of the penetrating epoxy resin adhesive prepared in this embodiment in stone processing includes at least one of bonding stone, repairing substrates, filling cracks, and brightening and repairing finishes, wherein the stone includes at least one of marble and granite, as detailed below: 1. Stone micropore penetration reinforcement: The penetrating epoxy resin adhesive is brushed or injected into the stone micropores. It penetrates into the stone through capillary action, and after curing, it seals the pores. The adhesive layer is transparent and does not cover the natural texture of the stone, thereby improving the overall strength of the stone.

[0047] 2. Underwater / Damp Stone Bonding: The pool and landscape stone are directly immersed in penetrating epoxy resin adhesive. The application can be carried out directly when there is a water film or water accumulation on the substrate surface. The curing is completed underwater, and the finished product is transparent and beautiful and does not easily yellow over long-term outdoor use.

[0048] 3. Crack repair: Penetrating epoxy resin adhesive is injected into the micro-cracks of the stone, and the repair marks are not obvious.

[0049] 4. Surface Repair: Apply penetrating epoxy resin adhesive to repair damaged areas of the stone. After curing, it has high gloss, is colorless and transparent, and is resistant to yellowing, restoring the original decorative effect of the stone to the greatest extent. It is suitable for outdoor landscape stone projects.

[0050] Comparative Example 1 An epoxy resin adhesive is basically the same as that in Example 1, except that only bisphenol F type epoxy resin is used.

[0051] Comparative Example 2 An epoxy resin adhesive is basically the same as that in Example 1, except that only AGE is used as the reactive diluent.

[0052] Comparative Example 3 An epoxy resin adhesive is basically the same as that in Example 1, except that a polyamide curing agent (polyamide 500) is used instead of a modified cycloaliphatic amine curing agent.

[0053] Comparative Example 4 An epoxy resin adhesive is basically the same as that in Example 1, except that no yellowing resistant additive is added.

[0054] The performance of the penetrating epoxy resin adhesives and reinforcing layers prepared in Example 1 and Comparative Examples 1-4 was tested at 25°C using conventional methods.

[0055] Permeability test method: Fill a disposable PE cup (approximately 90mm in diameter and 80mm in height) with fine sand, filling the cup to two-thirds full. Then pour the penetrating epoxy resin adhesive into the PE cup to conduct a penetration test. Record the penetration time and depth during the experiment.

[0056] The results show: Example 1 Test Results: Viscosity at 25℃: 29 mPa s, shear strength 9.3MPa, no whitening or bubbles after complete curing in wet conditions, gloss 109GS, Shore hardness 74D, colorless, transparent with low haze, QUV1000h Δb=1.0, excellent resistance to yellowing; penetration depth in fine sand is 70mm.

[0057] Comparative Example 1: Viscosity at 25℃: 48 mPa s, shear strength 9.4MPa, curable, gloss 107GS, Shore hardness 75D, transparent, QUV1000h Δb=1.2; penetration depth in fine sand is 70mm.

[0058] Comparative Example 2: Viscosity 26 mPa at 25℃ s, shear strength 7.8MPa, can be cured in water, gloss 105GS, Shore hardness 65D, transparent, insufficient strength, QUV1000h Δb=1.3; penetration depth in fine sand is 70mm.

[0059] Comparative Example 3: Viscosity 380 mPa at 25℃ s, shear strength 8.9MPa, sticky and white after curing, gloss 103GS, Shore hardness 73D, cloudy, QUV1000h Δb=4.5, severe yellowing; penetration depth in fine sand is 32mm.

[0060] Comparative Example 4: Viscosity at 25℃: 29 mPa s, shear strength 9.2MPa, fully cured, gloss 108GS, Shore hardness 74D, colorless and transparent, QUV1000h Δb=4.1, obvious yellowing; penetration depth in fine sand is 70mm.

[0061] From the above data, we can see that: In Comparative Example 1, the addition of only bisphenol F epoxy resin reduced the viscosity, but the viscosity did not exceed 50 mPa. However, due to the high price of bisphenol F epoxy resin, the cost is relatively high, making it unsuitable for widespread use.

[0062] In Comparative Example 2, only AGE was used as an active diluent. Although it could reduce viscosity, its shear strength was low, and it had defects such as insufficient strength.

[0063] In Comparative Example 3, replacing the modified alicyclic amine curing agent with a polyamide curing agent can improve the shear strength, but it cannot reduce the viscosity, resulting in poor permeability. In addition, it cannot improve the yellowing resistance and yellowing is prone to occur.

[0064] In Comparative Example 4, no yellowing resistance additive was added, so the yellowing resistance performance could not be improved, and yellowing was likely to occur.

[0065] In stark contrast, the penetrating epoxy resin adhesive obtained in Example 1 meets all performance requirements and possesses advantages such as low viscosity, high permeability, high shear strength, water neutralization and moisture curing, colorless and transparent cured products with excellent resistance to yellowing, high gloss, and moderate hardness. It is a novel adhesive with excellent comprehensive performance.

[0066] The results above show that, compared with existing conventional epoxy resin stone repair adhesives, the penetrating epoxy resin adhesive of this invention uses bisphenol F type epoxy resin combined with bisphenol A type epoxy resin and trimethylolpropane triacrylate as the main matrix, and employs two colorless and transparent AGE and benzyl glycidyl ether compounded reactive diluents, combined with a modified cycloaliphatic amine aqueous moisture curing system, supplemented with refractotropic matched silane activated fumed silica as a reinforcing filler, and compounded with ultraviolet absorbers and hindered amine light stabilizers to form a yellowing-resistant system. It also incorporates colorless and transparent anti-hydrolysis additives and transparent flexible toughening agents to construct a two-component epoxy adhesive system. Under the combined action of these components, the penetrating epoxy resin adhesive possesses advantages such as low viscosity, high penetration, high shear strength, water-neutralization and moisture curing, colorless and transparent cured products with excellent yellowing resistance, high gloss, and moderate hardness. Specifically, the viscosity at 25℃ is 20-35 mPa. The shear strength (24h) is ≥8.5MPa. It can be cured under moist conditions, producing a colorless, transparent, non-whitening, and non-bubbling cured film. The gloss of the cured product is greater than 100GS, and the Shore hardness is controlled at 70-80D. Furthermore, this penetrating epoxy resin adhesive exhibits excellent microporous penetration ability in natural stones such as marble and granite. It is suitable for bonding damp substrates and underwater stone, repairing cracks, reinforcing micropores, and restoring finishes. The adhesive layer is colorless and transparent, does not easily yellow over long-term use, does not obscure the natural texture of the stone, and balances bonding strength, toughness, and long-term decorative appearance. The raw materials are readily available, making it suitable for industrial production.

[0067] The above embodiments are merely preferred embodiments of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A penetrating epoxy resin adhesive, characterized in that, Includes component A and component B; Component A comprises the following raw material components in parts by weight: 15 to 25 parts of bisphenol F type epoxy resin 29 to 35 parts of bisphenol A type epoxy resin. 11 to 15 parts of trimethylolpropane triacrylate 12 to 18 parts of reactive diluent 3 to 6 parts of filler 1 to 2 parts of silane coupling agent; Defoamer 0.3 to 0.8 parts, 0.2 to 0.5 parts of wetting and dispersing agent; Yellowing resistance additive: 0.8 to 1.5 parts; Component B comprises the following raw material components in parts by weight: 70-80 parts of modified cycloaliphatic amine curing agent, 5 to 8 parts of curing accelerator, 8 to 12 parts toughening agent 2 to 4 parts of anti-hydrolysis additive; The active diluent is a compound of AGE and benzyl glycidyl ether; The yellowing resistance additive is a compound of hindered amine light stabilizer and benzotriazole UV absorber; The modified alicyclic amine curing agent is prepared from alicyclic amines and diluents as raw materials; The anti-hydrolysis agent is prepared from γ-aminopropyltriethoxysilane and a diluent.

2. The penetrating epoxy resin adhesive according to claim 1, characterized in that, The epoxy equivalent of the bisphenol F type epoxy resin is 160 g / eq to 180 g / eq; the epoxy equivalent of the bisphenol A type epoxy resin is 180 g / eq to 195 g / eq.

3. The penetrating epoxy resin adhesive according to claim 1, characterized in that, The active diluent is composed of AGE and benzyl glycidyl ether in a mass ratio of 1.85 to 2.15:

1.

4. The penetrating epoxy resin adhesive according to claim 1, characterized in that, The filler is fumed nano-silica with a surface modified by a silane coupling agent; the particle size of the fumed nano-silica is 20 nm to 50 nm.

5. The penetrating epoxy resin adhesive according to claim 1, characterized in that, The silane coupling agent is KH-560; the defoamer is BYK-054; the wetting and dispersing agent is BYK-142; the mass ratio of the hindered amine light stabilizer to the benzotriazole UV absorber is 1:1; the hindered amine light stabilizer is UV-531; and the benzotriazole UV absorber is UV-1500.

6. The penetrating epoxy resin adhesive according to claim 1, characterized in that, The preparation method of the modified alicyclic amine curing agent includes the following steps: adding the alicyclic amine to a three-necked flask, starting the stirrer, controlling the rotation speed at 75 rpm to 85 rpm, adjusting the temperature at 60℃ to 65℃, adding the diluent dropwise over a time of 2 hours to 2.5 hours, adjusting the temperature to 65℃ to 70℃ after the addition is complete, continuing to stir for 1 hour to 1.5 hours, filtering, and obtaining the modified alicyclic amine curing agent; the weight ratio of the alicyclic amine to the diluent is 284:130; the alicyclic amine is 1,3-BAC; and the diluent is epoxy resin diluent 501; The curing accelerator is 2-ethyl-4-methylimidazol; The toughening agent is polypropylene glycol diglycidyl ether; The preparation method of the anti-hydrolysis additive includes the following steps: adding γ-aminopropyltriethoxysilane to a three-necked flask, starting the stirrer, adding the diluent in two portions, reacting for 20 minutes after each addition, filtering, and obtaining the anti-hydrolysis additive; the weight ratio of γ-aminopropyltriethoxysilane to the diluent is 442:130; the diluent is epoxy resin diluent 501.

7. The penetrating epoxy resin adhesive according to any one of claims 1 to 6, characterized in that, The weight ratio of component A to component B is 3:

1.

8. A method for preparing a penetrating epoxy resin adhesive as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Under light-protected conditions, bisphenol F epoxy resin, bisphenol A epoxy resin, and trimethylolpropane triacrylate are mixed and stirred for 5 min to 20 min. An active diluent and a wetting and dispersing agent are added, and the mixture is heated to 40℃ to 45℃ and stirred for 20 min to 30 min. A filler, a silane coupling agent, a defoamer, and an anti-yellowing agent are added, and the mixture is stirred for 30 min to 40 min. The mixture is then cooled and filtered to obtain component A. Under light-protected conditions, a modified cycloaliphatic amine curing agent and an anti-hydrolysis agent are mixed and stirred for 10 min to 20 min. A curing accelerator and a toughening agent are added, and the mixture is stirred for 10 min to 30 min at a temperature of 40℃ to 45℃ to remove bubbles, thus obtaining component B. S2. Mix components A and B, stir for 3 to 5 minutes, let stand for 1 to 3 minutes to degas, and obtain a penetrating epoxy resin adhesive.

9. The application of a penetrating epoxy resin adhesive as described in any one of claims 1 to 7 or a penetrating epoxy resin adhesive prepared by the preparation method described in claim 8 in stone processing.

10. The application according to claim 9, characterized in that, The application includes at least one of the following: bonding stone, repairing base surface, filling cracks, and brightening and repairing decorative surfaces; the stone includes at least one of marble and granite.